2014
DOI: 10.1075/wll.17.1.02com
|View full text |Cite
|
Sign up to set email alerts
|

The development of orthographic processing skills in children in early French immersion programs

Abstract: Children learning to read in two languages are faced with orthographic features from both languages, either unique to a language or similar across languages. In the present study, we examined how children develop orthographic processing skills over time (from grade 1 to grade 2) with a sample of Canadian children attending a French immersion program and we investigated the underlying factor structure of orthographic skills across English and French. Two orthographic processing tasks were administered in both l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…Although further work is needed to examine the dimensionality of Arabic orthographic knowledge, and orthographic processing generally, on a broader scale, these preliminary results suggest that lexical orthographic knowledge may be a unitary ability indicated by individuals' ability to distinguish correct versus incorrect spelling in Arabic. The unidimensionality of our findings is in accordance with findings by Commissaire et al (2014), who found a one factor model of orthographic knowledge to capture both lexical and sublexical tasks in both French and English, suggesting a common orthographic knowledge skill across languages and variables.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although further work is needed to examine the dimensionality of Arabic orthographic knowledge, and orthographic processing generally, on a broader scale, these preliminary results suggest that lexical orthographic knowledge may be a unitary ability indicated by individuals' ability to distinguish correct versus incorrect spelling in Arabic. The unidimensionality of our findings is in accordance with findings by Commissaire et al (2014), who found a one factor model of orthographic knowledge to capture both lexical and sublexical tasks in both French and English, suggesting a common orthographic knowledge skill across languages and variables.…”
Section: Discussionsupporting
confidence: 91%
“…This may be done by designing a wordlike task based on the orthographic and morphological patterns represented in this measure. Embedding these patterns in pseudowords would assist researchers in exploring the feasibility of assessing orthographic knowledge at the sublexical level in Arabic, similar to the studies by Cassar and Treiman (1997), Pacton et al (2001), Commissaire et al (2014), and Deacon et al (2013). This could be particularly informative for assessing children's tacit orthographic knowledge prior to formal reading instruction.…”
Section: Future Directionsmentioning
confidence: 97%
“…This cross-linguistic difference in cognitive processes during reading has critical implications for readers' acquisition of reading skills in L2, because they transfer the cognitive strategies already established in their L1 to L2 reading (Commissaire, Pasquarella, Chen & Deacon, 2014;Koda, 2005Koda, , 2007. An extensive body of L2 word recognition studies has documented the lasting influence of L1 word recognition processes even among advanced-level L2 readers.…”
Section: Introductionmentioning
confidence: 99%
“…B. alphabetisch oder logographisch). Andererseits gibt es auch Universalien, die für alle Schriftsprachen Gültigkeit haben (Perfetti & Verhoeven, 2017a (Chung et al, 2017;Chung et al, 2018;Commissaire et al, 2014;Kahn-Horwitz et al, 2014;Kim & Piper, 2019;Kuo et al, 2016;Shakkour, 2014;Wawire & Kim, 2018). Dabei zeigen sich besonders auf der Ebe-ne der hierarchiehöheren Leseprozesse Transferleistungen, wenig erstaunlich, handelt es sich dabei doch um konzeptuelles Wissen wie die Hinzuziehung von Vorwissen, die Inferenzziehung oder die Aktivierung von Textformatwissen (vgl.…”
Section: Cross-linguistische Einflussfaktoren Beim Lesenlernenunclassified